Architected lattices embedded with phase change materials for thermal management of high-power electronics: A numerical study. (25th January 2023) - Ahmed Qureshi, Zahid; Addin Burhan Al-Omari, Salah; Elnajjar, Emad; Al-Ketan, Oraib; Abu Al-Rub, Rashid
Highlights: TPMS-PCM based heat sinks under high heat flux were numerically investigated. The effect of TPMS structure type, PCM type, Applied Heat Flux and Heat Sink Material were studied. For gallium-TPMS heat sinks, the effect of TPMS structure was not pronounced. For docosane-TPMS heat sinks, the effect of TPMS was considerably significant. Docosane-TPMS heat sink severely underperformed than gallium-TPMS heat sink in controlling the heat sink base temperature. An increase in applied heat flux caused faster PCM melting time and higher maximum heat sink temperatures. Copper based TPMS heat sinks outperformed AlSi10Mg based heat sink owing to superior thermo-physical properties of copper. Abstract: The boom of additive manufacturing has opened the doors to manufacture complex architectures with ease. The ever-increasing demands of high computational power has garnered a lot of research interest in more advanced and efficient cooling systems. Recently, additively manufactured and mathematically modeled Triply Periodic Minimal Surface (TPMS) based lattices have found widespread attention as thermal conductivity enhancers for phase change materials (PCMs). In this numerical study, architected lattices based on TPMS structures and impregnated with PCM have been studied as heat sinks for potential application in high power electronics cooling application. To authors' best knowledge, heat sinks based on TPMS structures impregnated with PCM have never been studied for high heat flux/electronics cooling applications. Two TPMS structures i.e., IWP and Primitive have been selected as candidates based on reported work on TPMS-PCM composites performance in thermal energy storage applications. Two materials for architected lattices were considered i.e., Aluminum powder (AlSi10Mg) and Copper. Furthermore, two PCMs are taken into account, one an organic PCM (Docosane) and the other being a metallic PCM (Gallium metal). Besides, three values of applied heat flux replicating to-be-cooled electronic chips were considered i.e., 50 kW/m 2, 100 kW/m 2 and 150 kW/m 2 . The results indicated that TPMS structures can help in temperature mitigation under high heat flux conditions. In the case of metallic PCM, the performance of both Primitive and IWP structure came out to be nearly identical. Hence, there was no architecture effect noticed in heat transfer performance of the lattices at all the three heat flux values. However, in the case of paraffinic PCM, Primitive structure showed better performance than IWP due to superior natural convection of liquid PCM in Primitive structure. However, paraffinic PCM could not aid in temperature mitigation to a realistic value despite being embedded inside metallic TPMS lattice owing to its inferior thermo-physical characteristics even at the smallest value of the heat flux. Gallium based heat sink outperformed paraffinic PCM as expected for both IWP and Primitive cases. Moreover, Copper based TPMS structures outperformed their AlSi10Mg based counterparts in mitigating the heat sink temperature owing to its superior thermo-physical properties. Therefore, this study offers a perspective of possible utilization and advancement of heat sinks for electronics cooling application.